Postpartum glucose testing for women with gestational diabetes mellitus: Improving regional recall rates. Issue 3 (June 2015) - Carmody, L.; Egan, A.M.; Dunne, F.P.
Highlights: Gestational diabetes is associated with an elevated lifetime risk of glucose intolerance. Follow up oral glucose tolerance testing is recommended at 3–6 months postpartum. Multiple studies demonstrate poor recall rates of 5–60% worldwide. In this study a regional coordinator facilitated a favourable recall rate of 75%. This was achieved through written and verbal communication with each woman. Abstract: Our aim was to evaluate attendance for postpartum glucose testing among women attending five antenatal centres with a diagnosis of GDM in the preceding pregnancy. A central, regional coordinator who made verbal and written contact with each individual facilitated a favourable recall rate of 75%.